The prognostic significance of troponin level in patients with malignancy (NIHR Health Informatics Collaborative TROP-MALIGNANCY study). (3rd October 2022) - Kaura, A; Samuel, N A; Roddick, A J; Glampson, B; Mulla, A; Davies, J; Woods, K; Patel, R S; Shah, A M; Perera, D; Channon, K M; Shah, A S V; et al.
Abstract: Background: Cardiac troponin is commonly raised in patients with malignancy and may aid clinicians in risk prediction. The prognostic significance of raised troponin in these patients with known malignancies remains unclear. Purpose: We sought to investigate the relation between troponin and mortality in a large, well characterised cohort of patients undergoing cardiac troponin testing with a concomitant malignancy. Methods: A retrospective cohort study was carried out using the National Institute for Health Research Health Informatics Collaborative Cardiovascular dataset of all consecutive patients who had a troponin measured at five hospitals between 2010 and 2017. Patients with a primary inpatient diagnosis of malignancy who had at least one cTn measurement during their hospital stay were identified. Patients were classified into solid tumour or haematological malignancy subgroups. Survival analyses were performed using multivariate Cox regression analyses and Kaplan-Meier plots. Cox regression analyses were adjusted for age, gender, C-reactive protein, haemoglobin, platelet count, white cell count, acute coronary syndrome, diabetes mellitus, heart failure, chronic kidney disease, chronic obstructive pulmonary disease, atrial fibrillation and angiography. The peak cTn level (highest level measured), standardised to the upper limit of normal (ULN), was used for all analyses. Results: 5571 patients undergoing troponin testing had a primary diagnosis of malignancy and comprised of twenty-one different cancer types. 4649 patients were diagnosed with solid tumours and 922 patients were diagnosed with haematological malignancies. Patients with raised troponin had a higher burden of cardiovascular comorbidities compared to patients with a troponin level below the ULN. The median follow-up in the cohort was 14 months (interquartile range 2–39 months). At 1-year follow-up, 2495 (42%) of patients died. Figure 1 shows Kaplan-Meier plots for patients stratified by troponin level. Patients with a troponin level ≥1xULN had a higher risk of death compared to patients with a troponin level <1xULN (Figure 1A). A similar trend was shown in cancer subtypes (Figure 1B, C). Raised troponin was an independent predictor of mortality in all patients with malignancy (adjusted hazard ratio 1.66, 95% confidence interval [CI] 1.52–1.81), in solid tumours (adjusted hazard ratio 1.63, 95% CI 1.48–1.81) and in haematological malignancy (adjusted hazard ratio 1.75, 95% CI 1.44 to 2.13) when compared to patients with a troponin level <1xULN. Conclusion: A raised troponin was associated with an increased mortality risk in patients with malignancy regardless of cancer subtype. Stratification of mortality risk using troponin may help guide clinicians in making management decisions for patients with malignancy. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): NIHR Imperial Biomedical Research Centre, as part of the NIHR Health Informatics Collaborative, and 2) British Heart Foundation